Giant strain tunability in polycrystalline ceramic films via helium implantation - A. Blázquez Martínez; S. Glinšek; T. Granzow; J.-N. Audinot; P. Fertey; J. Kreisel; M. Guennou; C. Toulouse (APL Materials)
Strain engineering is a powerful tool routinely used to control and enhance properties such as ferroelectricity, magnetic ordering, or metal–insulator transitions. Epitaxial strain in thin films allows manipulation of in-plane lattice parameters, achieving strain values generally up to 4%, and even above in some specific cases. In polycrystalline films, which are more suitable for functional applications due to their lower fabrication costs, strains above 1% often cause cracking. This poses challenges for functional property tuning by strain engineering. Helium implantation has been shown to induce negative pressure through interstitial implantation, which increases the unit cell volume and allows for continuous strain tuning with the implanted dose in epitaxial monocrystalline films. However, there has been no study on the transferability of helium implantation as a strain-engineering technique to polycrystalline films. Here, we demonstrate the technique’s applicability for strain engineering beyond epitaxial monocrystalline samples. Helium implantation can trigger an unprecedented lattice parameter expansion up to 3.2% in polycrystalline BiFeO3 films without causing structural cracks. The film maintains stable ferroelectric properties with doses up to 1015 He cm−2. This finding underscores the potential of helium implantation in strain engineering polycrystalline materials, enabling cost-effective and versatile applications.